Unmasking the heterogeneity of carbohydrates in heartwood, sapwood, and bark of Eucalyptus. (15th June 2020) - Xiao, Ming-Zhao; Chen, Wei-Jing; Cao, Xue-Fei; Chen, Yue-Ying; Zhao, Bao-Chen; Jiang, Zhi-Hua; Yuan, Tong-Qi; Sun, Run-Cang
Highlights: Carbohydrates in different tissues of Eucalyptus have been investigated. Raman spectra revealed the distribution of structural carbohydrates in situ . The sapwood cellulose had the highest degree of crystallinity. The heartwood hemicelluloses had higher xylose content, lower degree of branching. Abstract: In this study, the cellulose and hemicelluloses in heartwood, sapwood, and bark of E. urophylla × E. grandis were comprehensively investigated. The ultrastructural topochemistry of carbohydrates in cell walls was examined in situ by confocal Raman microscopy. Cellulose and alkali-extractable hemicelluloses samples were isolated from different tissues and comparatively characterized by compositional carbohydrate analyses, determination of molecular weights, FT-IR spectroscopy, and XRD and NMR techniques. It was found that among all of the samples, heartwood cellulose had the highest molecular weight as well as the lowest degree of crystallinity. Meanwhile the hemicelluloses in heartwood had higher xylose content, lower degree of branching, slightly lower molecular weights but narrower polydispersity than those in sapwood. The eucalyptus hemicelluloses mainly consisted of (1→4)-β-D -xylan backbone with glucuronic acid side chains. Furthermore, the hemicelluloses isolated from sapwood had a higher degree of substitution with terminal galactose than those isolated from heartwood and bark.